The Impact of Online Learning on the Learning Interest of Students at Anak Bangsa Christian High School in Surabaya - Rumiyati, Rumiyati; Kusumanigrum, Aprilia Dyah; Purba, Nursenta Dahliana; Binar, Sri (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
Learning interest is an internal drive that motivates individuals to learn something willingly and without coercion, leading to optimal learning outcomes. Online learning, on the other hand, refers to the teaching and learning process conducted without face-to-face interaction, supported by internet access and technological devices such as smartphones, laptops, or computers. The implementation of online learning during the pandemic has had varying effects on students' learning interest. This study aims to determine whether online learning influences the learning interest of students at Anak Bangsa Christian High School in Surabaya and to measure the extent of its impact. A quantitative method was employed in this research, with data collected through questionnaires completed by 60 respondents, representing the student population of Anak Bangsa Christian High School. The findings indicate a positive correlation between online learning and the learning interest of these students. The study reveals that students' learning interest increased with the enhancement of online learning methods. The contribution of online learning to shaping the learning interest variable among students at Anak Bangsa Christian High School in Surabaya was 57.5%. The study concludes that well-structured online learning can have a positive impact on students' learning interest. Online learning, when implemented interactively and creatively and supported by appropriate resources, can serve as an alternative learning system for the future, allowing students to more easily pursue study programs aligned with their talents and interests.